Curcumin inhibits cerebral ischaemia-reperfusion injury and cell apoptosis in rats through the ERK-CHOP-caspase-11 pathway - Yue Chen; Lixia Zhang; Zengtai Yang; Jie Yu (Taylor & Francis Group, 2022)
Context Curcumin has a significant effect on cerebral ischaemia-reperfusion injury (CIRI). However, the underlying mechanism is less studied.Objective This study investigates the role and mechanism of curcumin in CIRI.Materials and methods CIRI model Sprague-Dawley rats were divided into model, positive control and curcumin low/middle/high dose (50, 100 and 200 mg/kg/d) groups (n = 10 each). Drug intervention was administered by gavage once a day for 4 weeks. We calculated the neurobehavioural score and observed the cerebral infarct volume. Glial cytopathological changes were observed after haematoxylin-eosin staining. Apoptosis was detected by TUNEL (TdT mediated dUTP nick end labelling). Extracellular signal-regulated protein kinase (ERK), C/EBP-homologous protein (CHOP) and caspase-11 mRNA were detected by real-time PCR. Phosphorylated ERK (p-ERK), phosphorylated CHOP (p-CHOP) and caspase-11 were detected by Western blot. Superoxide dismutase (SOD) activity was detected by xanthine oxidation method; malondialdehyde (MDA) content by thiobarbituric acid colorimetry; and, glutathione (GSH) by spectrophotometry.Results Compared with control, the neurobehavioural scores, neuronal apoptosis, MDA, IL-1β, IL-18, mRNAs and protein levels of ERK/p-ERK, CHOP/p-CHOP and caspase-11 in model group were significantly higher (p < 0.01). Compared with model, the positive control and medium/high dose curcumin groups were significantly lower (p < 0.01). However, SOD and GSH decreased significantly in model group but increased significantly in positive control and medium/high dose curcumin groups (p < 0.01). Moreover, curcumin significantly alleviated ischaemic state and neuroinflammation (p < 0.01).Discussion and conclusions Curcumin may alleviate CIRI through ERK-CHOP-caspase-11 pathway. Our results may provide new insights into the pathogenesis of CIRI, and contribute to the development of treatment strategies for CIRI.